The Border and Its Bodies The Embodiment of Risk Along the U.S.-México Line - McGuire, Randall H.; Sheridan, Thomas E. (University of Arizona Press, 2019)
The Border and Its Bodies examines the impact of migration from Central America and México to the United States on the most basic social unit possible: the human body. It explores the terrible toll migration takes on the bodies of migrants-those who cross the border and those who die along the way-and discusses the treatment of those bodies after their remains are discovered in the desert.The increasingly militarized U.S.-México border is an intensely physical place, affecting the bodies of all who encounter it. The essays in this volume explore how crossing becomes embodied in individuals, how that embodiment transcends the crossing of the line, and how it varies depending on subject positions and identity categories, especially race, class, and citizenship.Timely and wide-ranging, this book brings into focus the traumatic and real impact the border can have on those who attempt to cross it, and it offers new perspectives on the effects for rural communities and ranchers. An intimate and profoundly human look at migration, The Border and Its Bodies reminds us of the elemental fact that the border touches us all.